2007
DOI: 10.1158/1078-0432.ccr-06-2878
|View full text |Cite
|
Sign up to set email alerts
|

Antiestrogen Therapy Is Active in Selected Ovarian Cancer Cases: The Use of Letrozole in Estrogen Receptor–Positive Patients

Abstract: Purpose: To evaluate the efficacy of the aromatase inhibitor letrozole in preselected estrogen receptor (ER)^positive relapsed epithelial ovarian cancer patients and to identify markers that predict endocrine-sensitive disease. Experimental Design: This was a phase II study of letrozole 2.5 mg daily until clinical or marker evidence of disease progression in previously treated ER-positive ovarian cancer patients with a rising CA125 that had progressed according to Rustin's criteria. The primary end point was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
140
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 168 publications
(148 citation statements)
references
References 26 publications
(18 reference statements)
5
140
1
2
Order By: Relevance
“…C, control; T, trastuzumab; P, pertuzumab. little information on the action or interaction of these agents in ovarian cancer, even though they have shown promise for some patients in the clinic (19,20,24). When combined, trastuzumab and pertuzumab show an enhanced antitumor activity in ovarian cancer xenografts, as they do in breast (38,39) and non-small-cell lung cancer xenografts (39 molecular phenotype and therefore responsiveness to other therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C, control; T, trastuzumab; P, pertuzumab. little information on the action or interaction of these agents in ovarian cancer, even though they have shown promise for some patients in the clinic (19,20,24). When combined, trastuzumab and pertuzumab show an enhanced antitumor activity in ovarian cancer xenografts, as they do in breast (38,39) and non-small-cell lung cancer xenografts (39 molecular phenotype and therefore responsiveness to other therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Another target that may have clinical utility in ovarian cancer is the estrogen receptor a (ERa). Phase II trials of aromatase inhibitors (AI) in ovarian cancer have shown modest response but rather better disease stabilization rates, especially when patients are selected on the basis of ERa expression (24). These results suggest that targeted therapies are feasible in ovarian cancer, but rational selection of both targets and patients is required to maximize patient benefit and reduce overtreatment.…”
Section: Introductionmentioning
confidence: 99%
“…Recent clinical data support the modest efficacy of aromatase inhibition in preselected ER-positive patients with ovarian cancer, supporting a possible role for hormonal manipulation. 31 Likewise, the hypothesis that the inhibition of the andro- PFS indicates progression-free survival; PFS1, time interval from the initiation of primary therapy to the date of first disease recurrence; 95% CI, 95% confidence interval; PFS2, PFS for patients receiving protocol therapy in second disease remission; PFS3 or 4, PFS for patients receiving protocol therapy in third or fourth disease remission. PFS indicates progression-free survival; PFS2, PFS for patients receiving protocol therapy in second disease remission; PFS1, time interval from the initiation of primary therapy to the date of first disease recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…IHC quantification of Rab35 expression could be an initial starting point in this context. As suggested in the study by Smyth and colleagues, selection of patients according to percentage of tumor cells expressing hormone receptors might be more informative on the efficacy of a trial drug than patient selection based only on the presence or absence of the receptor [78]. We, therefore, suggest that correlation of the response to treatment with percentage of AR-expressing tumor cells also be assessed in future trials.…”
Section: Discussionmentioning
confidence: 94%
“…For example, letrozole was evaluated as therapy for biochemically only (cancer antigen [CA]125) relapsing patients following primary chemotherapy. It was demonstrated that patients with tumors expressing high levels of ER had a better response to letrozole, suggesting that the efficacy of hormonal treatment is dependent not only on the presence of relevant receptors but also on their quantity [78]. Another target for endocrine therapy is the AR.…”
Section: Discussionmentioning
confidence: 99%